Leptospira interrogans: cinética da infecção e avaliação da proteção conferida por LigA - Coutinho, Mariana Loner (2011)
Leptospira interrogans is the usual causative agent of leptospirosis, a zoonosis that is endemic in tropical countries like Brazil and India. The available vaccines are bacterin-based from the more prevalent serovars to the vaccinated specie, but these vaccines do not develop long-lasting immunity or cross-protection. Subunit vaccines with recombinant proteins have the potential to generate an efficient leptospirosis vaccine. LigA is a protein that has adhesin function to the host and has been reported as protective against lethal challenge of Leptospira interrogans. The first part of this document defines a three-segment protective region of LigA constituted as domains 11 and 12, added of domains 10 or 13. The vaccine effect was evaluated based on pathology, humoral immune response and kidney leptospiral burden. The second part of this work aims to point out the importance of the correct understanding of the Leptospira interrogans infection kinectics to elucidate how the organism reacts in the first phase of the leptospiral infection. This evaluation is accessed by leptospiral load quantification in key-organs such as kidneys, liver, lungs and spleen, and by the evolution of the disease by hemmogram and biochemical analysis.